The Influence Of Motivation, Work Environment, And Competency On Asn Performance In The Public Works, Spatial Planning, Housing And Settlement Area (Putrpkp) Enviroment Of Takalar District - Muliyadi Amir; Andi Mappatompo Badawi; Dg. Maklassa Dg. Maklassa (Green Publisher Indonesia, 2024)
The Influence of Motivation, Work Environment, and Competence on the Performance of Civil Servants in the Public Works, Spatial Planning, Housing and Settlement Areas Office (PUTRPKP) of Takalar Regency, guided by Andi Mappatompo Badawi and Dg. Maklassa. This study aims to analyze and explain the Influence of Work Motivation, Work Environment, and Competence on the Performance of Civil Servants in the Public Works, Spatial Planning, Housing and Settlement Areas Office (PUTRPKP) of Takalar Regency. This type of research is quantitative research, which is research based on data that can be calculated to produce a solid assessment using SPSS. This study used 68 respondents using multiple linear analysis techniques. The results of this study show that work motivation has a significant positive influence on ASN performance with P = 0.007 < 0.05 with a coefficient value of 0.380. The work environment has a positive and insignificant influence on ASN performance with P = 0.502 > 0.05 with a coefficient value of 0.118. Competence has a significant positive influence on ASN performance with P = 0.024 < 0.05 with a coefficient value of 0.280. The Work Motivation variable is the most dominant variable that affects ASN Performance.